CALCULATING COLONY OF Candida spp. AMONG CHILDREN WITH INTELLECTUAL DISABILITY IN CIREBON - Dhini Oktaviani; Amanah Amanah; Eni Suhaeni; Risnandya Primanagara (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Children and adults with Intellectual Disability and Autism Spectrum Disorders (ASD) have decreased intestinal permeability and enzyme activity, causing gastrointestinal (GI) problems that are more frequent and more severe than in children from the general population. The immune system which is part of the intestinal barrier in children with Intellectual Disability (ID) experiences various disorders and becomes more susceptible to fungal invasion, such as Candida spp. This present study aims to calculate the colony of Candida spp. in the digestive tract of Children with Intellectual Disability (ID) in the city of Cirebon.Method: This is an observational study with cross-sectional design using purposive sampling. The study was conducted in November 2018-February 2019. The sample (ID) group consists of 31 individuals from Special Needs School and 60 individuals from National elementary school (non-ID) in the city of Cirebon. The inclusion criteria were children ages 6-12 years and the exclusion criteria were children under antifungal treatment and children under cytotoxic or immunosuppressive drugs. The fecal samples from the ID group and non-ID were examined at the Laboratory of the Faculty of Medicine, Universitas Swadaya Gunung Jati Cirebon, Indonesia using Digital Colony counter. Collected data were stored and analyzed using computer aided Statistical program. Mann-Whitney analysis of variance techniques were used to test the hypotheses. Results: The results showed that there are significant differences in the colonies of Candida spp. between the ID group and non-ID group. Median colony of Candida spp. in the ID group is 39.00 with mean colony of 126.90 while the median colony of non-ID group is 3.00 with mean colony of 40.93 (p<0.001).Conclusion: There are significant differences between the Candida spp. colonies in the ID group with the non-ID.